Testiculer detorsion in children: Preliminary results - Saraç, Mehmet; Bakal, Ünal; Tartar, Tugay; Gürbaz, Mustafa Tamer; Onur, Mehmet Ruhi; Kazez, Ahmet (Logos Medical Publishing, 2014)
Objective: Testicular torsion is a urological emergency, most frequently occurring in the newborns and at the puberty. Its most frequent morbidities are the loss of testis and infertility. This study aimed to present preliminary clinical and radiological results of detorsion in testicular torsion. Material and Methods: Seventeen patients who were treated in our clinic for testicular torsion between January 2007 and December 2012 were analyzed retrospectively. Scrotal doppler ultrasonography (US) findings, surgical results and early follow-up were recorded. Results: The mean age of the patients was 8,5 years (range: 1 day - 15 years), and three of them were newborns. The mean time at admission was 23 hours (range: 6 hours - 3 days). The most frequent symptoms were testicular pain and swelling, and vomiting. Scrotal doppler US was descriptive in all patients. Four (23 %) patients had orchiectomy while 13 had detorsion and fixation. The contralateral testis was also fixated in all patients. A 3-year mean follow up period revealed reduction in the testis size in 5 patients (38 %) and atrophy in one (8 %) patient, in 13 patients who had detorsion. Patients with atrophied testes were admitted late and had a torsion more than 360 degrees. Conclusion: Detorsion and fixation may not cause significant changes in testicular volumes and blood supply if the patient is admitted within 24 hours and the torsion isn't more than 360 degrees. Although orchiectomy is frequently performed in newborn testicular torsion, detorsion and fixation may be used as an alternative management in adolescents. © Cocuk Cerrahisi Dergisi. All rights reserved.
Çocuklarda testiküler detorsiyonun ön sonuçları
Keywords: Detorsion; Testis; Torsion